2008
DOI: 10.1109/temc.2008.926888
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude Probability Distribution Measurement for Electric Field Intensity Assessment of Cellular-Phone-Base Stations

Abstract: In compliance assessments of radio-frequency exposure from cellular-phone-base station antennas, the root of 6-min time average of the squared electric fields is commonly required. Under the assumption that the time-varying electric fields belong to an ergodic process, a new approach has been proposed to estimate the 6-min time average from the ensemble average of the squared electric fields based on amplitude probability distribution (APD) measurements for a shorter time, much less than 6 min. The usefulness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Studies have reported the development of procedures, prediction formulas and instrumentation for assessing the SAR and radio frequency electromagnetic fields (RF-EMFs) of base station antennas, in terms of the antenna parameters, distance and time variations and amplitude probability of exposure levels [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the development of procedures, prediction formulas and instrumentation for assessing the SAR and radio frequency electromagnetic fields (RF-EMFs) of base station antennas, in terms of the antenna parameters, distance and time variations and amplitude probability of exposure levels [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%